2004
DOI: 10.1063/1.1818732
|View full text |Cite
|
Sign up to set email alerts
|

Density of states determination from steady-state photocarrier grating measurements

Abstract: We present a method to obtain the density of states (DOS) of photoconductive insulators based on steady-state photocarrier grating (SSPG) measurements. A simple expression—relating the DOS at the electron quasi-Fermi level to measurable quantities—is deduced by performing suitable approximations from the analytical solution of the generalized equations that describe the SSPG experiment. The validity of the approximations and the applicability of the final expression are verified from numerical simulations of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In recent publications we have shown that it is possible to deduce some part of the DOS distribution, interacting with the majority carriers, from the value of ␤ taken at large grating periods ͑␤ lim ͒. 6,7 We obtained the following relation:…”
Section: The Above Expression Closely Resembles Expression ͑1͒mentioning
confidence: 86%
“…In recent publications we have shown that it is possible to deduce some part of the DOS distribution, interacting with the majority carriers, from the value of ␤ taken at large grating periods ͑␤ lim ͒. 6,7 We obtained the following relation:…”
Section: The Above Expression Closely Resembles Expression ͑1͒mentioning
confidence: 86%
“…( 10) we do not obtain directly the density of states from the experimental data, but rather the quantity N(E tn ) Â c n / l n . This quantity is also obtained from the modulated photocurrent (MPC) technique performed in the high frequency range and from the recently proposed method to extract the DOS from SSPG measurements [17,18]. Thus, the validity of the c-DOS determination can be confirmed by comparing it to the MPC-DOS and SSPG-DOS obtained on the same a-Si : H sample by using the same standard values for c n and l n .…”
Section: Methodsmentioning
confidence: 95%
“…The main drawback of the second group of methods is that the DOS is only obtained over a limited energy range. In a recent publication 14 the authors presented a new method belonging to the second category, based on steady-state photocurrent grating ͑SSPG͒ measurements. In this work we discuss the method in more detail, presenting new experimental results for hydrogenated amorphous silicon samples.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, no attempts to derive the density of localized states directly from the application of a reconstruction formula to SSPG measurements had been presented until our recent paper. 14 This work is organized as follows. In Sec.…”
Section: Introductionmentioning
confidence: 99%